Development of hybrid microfluidics chip for water desalination and purification - Esmail Abdullah, Mohammed Basheer (2021)
Directional solvent extraction desalination (DSE) desalination method was introduced as an alternative, membrane-free desalination technique. Despite all the promising advantages of this technique, it is not further investigated or commercially applied due to two significant drawbacks that affect its efficiency. The first drawback is the massive and complicated mixing and separation steps. Additionally, the separation is simply a settling process, thus requiring time and vast space. The second drawback is the existence of solvent residuals in the effluent product water due to the poor selective decanting technique, which relies on gravitational forces. This study, for the first time, introduces the directional solvent extract (DSE) in a micro-scale system using microfluidics technology. The chip was designed with two sections for extraction and separation. In both parts, the liquids were separated using capillary channels perpendicular to the mainstream. The main channels were designed to be 400 μm in width and 100 μm in height. Two streams inlets will be introduced through a Y-junction, octanoic acid as the organic phase, and saltwater as the aqueous phase. The desalination performance was investigated at four different temperatures and five different solvent flow rates. The mixing efficiency and the integration with photocatalyst-based on the human-hair system were found to contribute significantly to overcome the two major drawbacks identified earlier where the flow in such systems is entirely dominated by the apparent physical properties like the surface tension and viscosity of the flowing liquids. The hybrid chip has shown a substantial performance in extracting water from the saltwater at low temperatures and by using octanoic acid as solvent. Using the capillary improved the water yield up to 47% at the average temperature and maximum solvent flow rate. Additionally, the product water salinity reduced with the capillary separation from 0.35% up to 0.04%, which is 83% lower than the salinity of the water product obtained at the macroscale. Besides, the solvent residuals reduced when using the microfluidics chip and were found to be as low as 13.5 ppm at 65 ℃ and the flow rate ratio of 2. Based on the results, it is believed that with appropriate temperature and integrated automated systems, this chip can be a future replacement to the current desalination methods. The development of such devices based on microfluidics offers a future easy and low energy water desalination, which can be used in any water scarcities region.